Indigenous Peoples, Land, and Conflict in Mindanao, Philippines - LUCIA MADRIGAL; JOSE CUESTA; SERGIO SOMERVILLE (Asian Development Review, 2025)
This paper explores the links between conflict, land, and indigenous peoples on the island of Mindanao in the southern Philippines. The analysis takes advantage of the unprecedented concurrence of data from the 2020 census, an independent conflict data monitor for Mindanao, and administrative sources on ancestral land titling for indigenous peoples in the Philippines. While evidence elsewhere compellingly links land titling with conflict reduction, we find a more nuanced story in Mindanao using mixed methods. Conflicts, including land- and resource-related conflicts, are generally less likely in districts with higher shares of indigenous peoples. Ancestral domain areas also have a lower likelihood of general conflict but a higher likelihood of land-related conflict. Our econometric findings suggest that ancestral domain titling does not automatically solve land-related conflicts. Only fully awarded ancestral domain titles are—weakly—associated with reductions in land-related conflict. However, when administrative delays occur, titling is associated with sustained, rather than decreased, conflict.